Impacts of the development of mineral metal resources on surface water quality in the Mongolian Plateau based on meta-analysis - Ma, Linqian; Liu, Huamin; Jing, Jin; Liu, Yang; Zhang, Rui; Xu, Zhichao; Qin, Wei; Kou, Xin; Cao, Xiaoai; Wen, Lu; Wang, Lixin (Frontiers in Environmental Science, 2022)
The mining of metal resources is one of the major sources of heavy metals in surface water, but studies on the different characteristics of the impact of the exploitation of mineral metal resources on surface water from a large-scale perspective are lacking. In the present study, we quantified the impacts of mineral metal resource development on As, Cu, Cr, Pb, Zn, Hg, Ni, Cd, Mn, and Fe in the overlying water and sediments of surface water under different scenarios (i.e., different geographic units and different mined metal types) using meta-analysis for the Mongolian Plateau of Mongolia and the Inner Mongolia Autonomous Region of China, which is rich in mineral metal resources and has high exploitation and use intensity. Finally, funnel plots and Egger’s regression analysis were used to test the publication bias of the data. The results show that the order of heavy metal content in the overlying water of the Mongolian Plateau was Fe > Mn > As > Zn > Cu > Pb > Cr > Ni > Cd > Hg, and the order of heavy metal content in the sediment was Fe > Mn > Zn > Cr > Pb > Ni > Cu > As > Cd > Hg. In addition, As, Cr, Zn, Hg, Cd, and Pb in overlying water exceeded the standard to different degrees, among which the contents of As and Pb were 1.4 and 1.3 times higher than the World Health Organization guideline, and the contents of Cr, Pb, Hg, Cd were 1.5, 1.3, 25.4, 2.6 times Chinese environmental quality standards for surface water, and the contents of As, Pb, Zn, Hg were 1.4, 1.3, 4.7, 12.7 times Mongolian water quality standards, respectively. The content of As in sediments was 2.6 times the background value of soil environmental quality in Inner Mongolia. Significant differences existed in the content of heavy metal pollutants in surface water of different countries; the content of heavy metals in the overlying water was significantly higher in Inner Mongolia Autonomous Region of China than in Mongolia. Copper and molybdenum polymetallic mines significantly increased the content of Cd, Cr, Cu, Fe, Hg, Pb, and Zn in the overlying water, while the content of As, Cr, Pb, and Zn in overlying water increased significantly due to lead–zinc mining. However, the mining of gold–silver, lead–zinc, copper–molybdenum, and other polymetallic mines all significantly affected the concentration of As in sediments. The results of the present study can provide data support for environmental protection and the restoration of surface water in metal mining areas of the Mongolian Plateau.